An approach to teaching and learning about Digital Transformation (Research, Society and Development, 2023)
Technological advances have made available in the last decade a set of exponential and disruptive technologies that have been promoting the digital transformation of society. It is a set of technologies associated with the concept of Industry 4.0. This article proposes an approach to teaching and learning about digital transformation. As methodological aspects of the work, the study is characterized as qualitative and exploratory. The proposed approach consists of a set of activities that can be followed in higher education disciplines that address topics related to innovation, entrepreneurship and the digital transformation itself. This set of activities is presented in the form of a process, in order to characterize a didactic resource that can be adopted in higher education disciplines. As part of this didactic resource, a mental map was also designed that illustrates the different areas of society that have been changing as a result of the digital transformation. The presented approach characterizes an alternative for teaching and learning about the influence of 4.0 technologies in different areas of society.